Estudo do Mobile-metagenome a partir de biblioteca metagenômica proveniente de solo com cultivo de cana-de-açúcar e solo de floresta - Pinto, Alessandra dos Santos [UNESP] (2015)
Mobile Genetic Elements (MGE) are segments of DNA present in the biological domains that have the ability to move around within a genome. They are considered key player in the evolution and diversification of living things. Insertion Sequences (IS) are the most abundant MGEs of prokaryotes. IS are compact elements that encode the gene responsible for the mobilization, the transposase. Comparative genomic studies indicate that the transposase is the most abundant gene found in public database of genomes and metagenomes. This study evaluated the abundance and diversity of transposases from high-throughput sequencing data originated from two metagenomic libraries, one from soil with sugarcane cultivation and the other from forest soil. The metagenomes were analyzed through two research fronts. In the first one, transposases were identified in a set of 267. 879. 464 reads paired-end (2x100bp) by MG RAST tool. In the second front of research, the reads of each metagenome were fitted (de novo assembly) and subsequently recorded by ISsaga 2.0 tool and platform MG-RAST. The platform MG- RAST identified 902.982 (reads) with allocated transposase function, whereas the 2.0 ISsaga tool recovered 592 (scaffolds) containing open reading frames (ORFs) coding for transposase. A total of 120 (22%) scaffolds and 767.534 (85%) reads noted were classified in different taxonomic groups resulting the phylum Proteobacteria (48% - MG-RAST and 34.3% - Issaga 2.0). Comparative analysis and biocuration indicate that 695.296 (77%) of the reads were incorrectly assigned with transposase function by MG-RAST tool. Among the families of transposase classified by Issaga 2.0, feature the families: IS110 (76 / 13.9%), IS3 (74 / 13.6%), and particularly 65 scaffolds (11.9%) from ISNCY family (not classified yet). Another noticeable result is that no IS previously described in the literature has been identified in these metagenomic data. This study revealed: (a) MG-RAST ...